The Children Right Violation in the Conflict of Sudan: Government Negligence - Yordan Gunawan; Danu Fernando; Rahmawati Mayta Wardani; Mohammad Hazyar Arumbinang (Fakultas Hukum, Universitas Warmadewa, 2024)
The conflict caused by the government's negligence in handling political issues that have an impact on the welfare of children's rights that should be obtained, research uses a normative approach method. By using the regulation of children's rights in the Convention on the Rights of the Child which is a universal principle and legal norm regarding the position of children and international human rights treaties, the purpose of research is to find out the causes of the loss of children's human rights caused by government negligence and how the implementation of international law and the contribution of UNICEF (United Nations International Children's Emergency Fund) in protecting children's rights, the Convention on the Rights of the Child is recognized as the most advanced human rights treaty, The Convention on the Rights of the Child is recognized as the most advanced human rights treaty agreed upon by states, the contribution of international humanitarian agencies that work with other international agencies to reduce or eliminate violence against children and provide special treatment for children who have mental disorders because see what children should not see, as an international organization UNICEF not only oversees and prevents the welfare of children but also determines the prospects for a decent and humane life for minors.